2018
DOI: 10.1002/jrs.5496
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new psychoactive substances (NPS) by Raman spectroscopy

Abstract: There is an increasing need of developing methods for fast recognition and identification of new psychoactive substances (NPS). The chemical identification of these new substances produced with the intention of mimicking the effects of controlled drugs is a challenge for forensic and Customs laboratories. In this study, we aim to test the potential of Raman spectroscopy for the identification and classification of seized Customs samples into three NPS families. The performance of two excitation wavelength lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 11 publications
5
37
0
Order By: Relevance
“…Both are well‐known effects in direct spectroscopic analysis on solid samples caused by particle size differences, light scattering, and spectral interferences. Spectral preprocessing is a common strategy to extract useful information from the raw spectral data and remove nonselective systematic and random signal fluctuations 24,25,37 . Figure 2 shows the (a) raw spectral data, (b) data after SNV preprocessing, (c) subsequent smoothing, and (d) a 1,560‐ to 1,756‐cm −1 selection with baseline correction for both cocaine HCl and cocaine base.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both are well‐known effects in direct spectroscopic analysis on solid samples caused by particle size differences, light scattering, and spectral interferences. Spectral preprocessing is a common strategy to extract useful information from the raw spectral data and remove nonselective systematic and random signal fluctuations 24,25,37 . Figure 2 shows the (a) raw spectral data, (b) data after SNV preprocessing, (c) subsequent smoothing, and (d) a 1,560‐ to 1,756‐cm −1 selection with baseline correction for both cocaine HCl and cocaine base.…”
Section: Resultsmentioning
confidence: 99%
“…Spectral preprocessing is a common strategy to extract useful information from the raw spectral data and remove nonselective systematic and random signal fluctuations. 24,25,37 Figure 2 shows the (a) raw spectral data, (b) data after SNV preprocessing, (c) subsequent smoothing, and (d) a 1,560-to 1,756-cm −1 selection with baseline correction for both cocaine HCl and cocaine base. Spectra of the cutting agents levamisole, paracetamol, and procaine are shown in the same plots to demonstrate the spectral selectivity.…”
Section: Spectral Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Their approach is applicable where an analyte is either a minor contributor or is spatially distributed on a strongly interfering substrate. Omar et al [ 175 ] reported the use of Raman to identify new psychoactive substances (NPS). Principal component analysis was employed to create a model that successfully discriminates three major NPS families.…”
Section: Pharmaceutical Food and Forensic Applicationsmentioning
confidence: 99%
“…For an extensive review on chemometric applications in forensics, refer to Silva et al [ 12 ] and Sena et al [ 18 ] Recently, three studies reported the use of Raman spectroscopy and Principal Component Analysis (PCA) to evaluate differences and similarities among NPS samples and improve chemical characterization. [ 15,19,20 ] In another study, [ 21 ] Partial Least Squares Discriminant Analysis (PLS‐DA) was employed to classify NPS infrared spectral data. Although these studies showed the great potential of the spectroscopic techniques to analyze a diversity of NPS samples, the chemometric models presented were not robust for field applications, and their performance was negatively influenced by the diversity of chemical components usually found in street NPS samples.…”
Section: Introductionmentioning
confidence: 99%